Clinical Reasoning: Survey of Teaching Methods and Assessment in Entry-Level Physical Therapist Clinical Education. Issue 3 (September 2018) - Huhn, Karen; Black, Lisa; Christensen, Nicole; Furze, Jennifer; Vendrely, Ann; Wainwright, Susan
Abstract : Background: Clinical reasoning skills have been identified as an integral part of physical therapist education developed in both the academic and clinical settings. There is limited understanding of clinical instructors (CIs) expectations related to the anticipated level of clinical reasoning (CR) skills achieved by students and how CR is taught and assessed in the clinic. Objective: The purpose of this research was to explore how CIs teach and assess student physical therapists' CR skills and garner an understanding of CIs' expectations related to CR skills attained at various levels of clinical experience. Design: A descriptive, cross-sectional survey was used to gather data from CIs. Methods: Participants identified from an American Physical Therapy Association database of credentialed CIs were asked to complete an 18-question electronically delivered survey. Results: A nationwide sample of 749 CIs completed the survey. The data clearly demonstrated that CIs value and recognize the importance of clinical education in the development of CR. They also value the use of engaged discussion and reflection to foster the development of reasoning skills. Most CIs did not expect students to achieve entry-level CR skills during the third year. Conclusions: Clinical instructors see the importance of clinical experiences and engaged discussion to foster the development of CR. Further research is needed to understand why most clinical educators did not expect students to achieve "entry-level" CR skills as defined by the Clinical Performance Instrument by the final year of the program. Abstract : Supplemental Digital Content is Available in the Text.